Stalinowska wojna partyzancka na Ukrainie 1941–1944, część 1 - Gogun, Aleksander (Pamięć i Sprawiedliwość, 2006)
The article describes soviet partisan movement in Ukraine during WW2, its main periods and directions of activity, organisation and leadership of partisans, manning, distinguishing features of communist partisans in comparison with Ukrainian insugrents (UPA) and AK (Polish Home Army). The stress was put on little known aspects of partisan movement: relationships with civilians, terror, robberies, marauding, scorched earth strategy, postscripts to diversion and military operations, struggle of soviet partisans and AK against Ukrainian nationalistic partisans. The article concentrates on conditions and causes of crushing defeat of partisan movement in the fi rst year of the war (1941/1942), a turning point in the second year (1942/1943) and impressive success of the third year of the war (1943/1944) reached in the environment of hostile west-Ukrainian citizens. The summary depicts structure, system distinguishing features of Stalin partisan movement in the Ukraine: its reckless, thus quite effective diversion and military activities, neglecting lives of partisans by their leadership, terror towards civilians ethnically similar to partisans, concious provoking occupants’ terror against civilians and lack of desire to defend them, long-term activity in conditions of hostile or neutral civilians, badly organised and thought over system of requisitions of food and other material values from civilians, high level of marauding and robberies, low morals of troops (drinking, sexual violence, low discipline), numerous inner conflicts. Such distinctions can be explained by a simple fact that soviet partisan movement was one of manifestations of belligerent stalinism.